Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Show that $$f(z)=\frac{\sin\sqrt z}{\sqrt z}$$ is an entire function of finite order $\rho$ and determine $\rho$.

I observed that the two determinations of the square root differ only for the signum. Since $\sin(-z)=-\sin z$, we have that $f(z)$ is well defined, and entire because it's the ratio of two entire functions with denominator never vanishing. For the order i use the Taylor expansion $$\sin z=\sum_{n=0}^{+\infty}(-1)^n\frac{z^{2n+1}}{(2n+1)!}$$ which for $z=\sqrt z$ gives $$\sin\sqrt z=\sum_{n=0}^{+\infty}(-1)^n\frac{z^{n}\sqrt z}{(2n+1)!}$$ Thus $$\frac{\sin\sqrt z}{\sqrt z}=\sum_{n=0}^{+\infty}(-1)^n\frac{z^{n}}{(2n+1)!}$$ Then we have $$(2n+1)!\geq2^n n!$$ hence $$|\frac{\sin\sqrt z}{\sqrt z}|\leq\sum_{n=0}^{+\infty}\frac{(\frac{|z|}{2})^{n}}{n!}=e^{|z|/2}$$

This (if correct) shows that $\rho\leq\frac{1}{2}$. How can be shown the identity?

share|improve this question
    
There are a few mistakes here. The series for $\sin z$ is not quite right. You mean: $$\sin z = \sum_{n=0}^{\infty} \frac{(-1)^nz^{n+1}}{(2n+1)!} \, . $$ When you change from the series for $\sin z$ to the series for $\sin \sqrt{z}$, you seem to change $z^{2n}$ to $z^n\sqrt{z}$. This isn't correct. $(\sqrt{z})^{2n} = (z^{1/2})^{2n} = z^{2n/2} = z^n$. In fact: $$\sum_{n=0}^{\infty} \frac{(-1)^nz^n\sqrt{z}}{(2n+1)!} = \frac{\sqrt{z}\sinh \sqrt{-z}}{\sqrt{-z}} \, . $$ –  Fly by Night Jan 9 '13 at 20:08
    
sorry, there was an error in the $sin z$ series, i've edited. thank you –  Federica Maggioni Jan 9 '13 at 20:09
    
Remember: You can use \sin \cos \tan \sec \cot and \csc for the trig' functions in LaTeX, i.e. $\sin z$ instead of $sin z$. –  Fly by Night Jan 9 '13 at 20:14

1 Answer 1

up vote 0 down vote accepted

To show $\rho \geq 1/2$, write

$$ f(z) = \frac{\sin \sqrt{z}}{\sqrt{z}} = \frac{e^{i\sqrt{z}}-e^{-i\sqrt{z}}}{2i\sqrt{z}} $$

and show that

$$ f(-x) \sim \frac{e^{\sqrt{x}}}{2\sqrt{x}} $$

as $x \to \infty$ with $x > 0$.

share|improve this answer
    
$f(-x)=\frac{e^{-\sqrt x} -e^{\sqrt x}}{-2\sqrt x}$, dividing this by $-\frac{e^{\sqrt x}}{2\sqrt x}$ i get something which tends to 1 as x goes to $\infty$. Hence $f(-x)$ is asymptotic to what you said. Now, why this implies the order of growth is greater then one-half? does asymptotic implies $ O(x^{1/2})$? –  Federica Maggioni Jan 9 '13 at 20:57
    
@FedericaMaggioni, If $f$ is of order $\rho$ then $$|f(z)| \leq C \exp(|z|^\rho)$$ for $|z|$ large enough, so that $$|f(z)| \exp(-|z|^\rho)$$ is bounded. In particular, $$|f(-x)| \exp(-x^\rho)$$ is bounded as $x \to \infty$. Now suppose $\rho < 1/2$ and use the asymptotic estimate. –  Antonio Vargas Jan 9 '13 at 21:10
    
substituting the asymptotic estimate in the last equation i get something which goes to infinite at numerator faster than denominator, contraddicting the boundness. –  Federica Maggioni Jan 9 '13 at 21:17
    
@FedericaMaggioni exactly. –  Antonio Vargas Jan 9 '13 at 21:17

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.